2009
DOI: 10.1001/jama.2009.1307
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Citations in Web of Science, Scopus, and Google Scholar for Articles Published in General Medical Journals

Abstract: ITATION COUNTS ARE USED TO measure the impact of articles, journals, and researchers and are frequently incorporated in decisions of academic advancement. However, the validity and methods behind the procurement of citation counts have received limited attention. Until relatively recently, Web of Science was the only practical way to obtain citation counts. 1 In the general medical literature, virtually all previous citation analysis studies have used this database exclusively 2-6 and checking the accuracy or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
463
0
29

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 685 publications
(503 citation statements)
references
References 17 publications
11
463
0
29
Order By: Relevance
“…[11][12][13] Web of Science provides a comprehensive indexing system for each author's address of papers included in the database. While Web of Science does not use a controlled vocabulary, it does provide a standardized, consistent method of indexing university names.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13] Web of Science provides a comprehensive indexing system for each author's address of papers included in the database. While Web of Science does not use a controlled vocabulary, it does provide a standardized, consistent method of indexing university names.…”
Section: Methodsmentioning
confidence: 99%
“…TorresSalinas, Lopez-Cozar, and Jimenez-Contreras (2009) found that articles in the area of the health sciences authored by researchers at the University of Navarra (Spain) received 14.7% more citations in Scopus than in the Web of Science. Kulkarni, Aziz, Shams, and Busse (2009) found that for articles published in general medical journals, Scopus retrieved more citations per article (median=149) than did Web of Science (median =122).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There have 115 been several studies comparing strengths and weakness of PubMed, Scopus, Web of Science and Google Scholar (Bakkalbasi et al, 2006;Bar-Ilan, 2008;Falagas et al, 2008;Kulkarni et al, 2009). Scopus research engine is selected because it is the largest abstract and database of peer-review literature (Burnham, 2006;De Moya-Anegón et al, 2007;Leydesdorff et al, 2010).…”
Section: Justification and Description Of Sourcesmentioning
confidence: 99%